Di-μ-oxido-bis[bis(diisopropylacetamidinato)-κN;κ2N,N′-germanium(IV)] - Frank T. Edelmann; Peter G. Jones; Edmund P. Burte; Cristian G. Hrib; Nancy Frenzel; Ronny Syre (Acta Crystallographica Section E, 2013)
The title compound, [Ge2(C8H17N2)4O2], crystallizes with imposed twofold symmetry, which allows the monodentate amidinate ligands to be arranged in a cisoid fashion. The independent Ge—O distances within the central Ge2O2 ring, which is essentially planar (r.m.s. deviation = 0.039 Å), are 1.7797 (8) and 1.8568 (8) Å. The germanium centres adopt a distorted trigonal–bipyramidal geometry, being coordinated by the two O atoms and by one bidentate and one monodentate amidinate ligand (three N atoms). One N-isopropyl group is disordered over two positions; these are mutually exclusive because of `collisions' between symmetry-equivalent methyl groups and thus each has 0.5 occupancy.